Peningkatan Pemahaman Ancaman Bencana di Kabupaten Subang pada Saka SAR Kabupaten Subang Melalui Edukasi Mitigasi Bencana - Akhmad Unggul Priantoro; Hayatul Khairul Rahmat; Agung Prihantoro; Bullion Dragon; Ayu Wahyuningtyas (Yayasan REDI Tiga Monas, 2024)
Subang Regency, which is located in West Java Province, is an area that is vulnerable to various natural disaster threats, such as floods, landslides and earthquakes. Dynamic geographical and climatic conditions place Subang Regency in a position that is vulnerable to disaster events. This community service activity aims to increase understanding of disaster threats in Saka SAR, Subang Regency through disaster mitigation education. Community service activities have been carried out well without significant obstacles and there is a conclusion that this community service activity has been carried out communicatively, as can be seen from the enthusiastic participants in the question and answer process, responding when asked questions and listening to explanations of the questions asked. given. With this training, it is hoped that the understanding of disaster threats in Saka SAR, Subang Regency, will increase through disaster mitigation education.